'I want my sons to be like dad' LAHAD DATU HERO: His widow is to receive UUM degree on his behalf next week - Singh Randhawan, Sharanpal (New Straits Times, 2013)
MOST children grow up watching and reading about their superheroes on television and in comic books, but the widow of Lahad Datu hero Assistant Superintendent Zulkifli Mamat has something else in mind for her sons.Noor Aziah Noor, 29, wants her children, especially her 51-day-old son, Noor Aqib Syahid, to grow up watching recordings of their father and listening to stories of his bravery. She has two other children: Noor Aqmar Amiruddin, 5, and Noor Muhammad Aqil, 2.